Serum homocysteine, arsenic methylation, and arsenic-induced skin lesion incidence in Bangladesh: A one-carbon metabolism candidate gene study. (April 2018) - Niedzwiecki, Megan M.; Liu, Xinhua; Zhu, Huiping; Hall, Megan N.; Slavkovich, Vesna; Ilievski, Vesna; Levy, Diane; Siddique, Abu B.; Kibriya, Muhammad G.; Parvez, Faruque; Islam, Tariqul; Ahmed, Alauddin; et al.
Abstract: Background: Inorganic arsenic (As) is methylated via one carbon metabolism (OCM) to mono- and dimethylated arsenicals (MMA and DMA), facilitating urinary excretion. Hyperhomocysteinemia (HHcys), a marker of impaired OCM, is a risk factor for As-induced skin lesions, but the influences of single nucleotide polymorphisms (SNPs) in OCM genes on Hcys, As metabolism and skin lesion risk is unclear. Objectives: To (i) explore genetic sources of Hcys and the causal role of HHcys in As-induced skin lesion development using OCM genetic proxies for HHcys and (ii) identify OCM SNPs associated with urinary As metabolite proportions and/or skin lesion incidence. Methods: We conducted a case-control study nested in the Health Effects of Arsenic Longitudinal Study (HEALS) in Bangladesh which 876 incident skin lesion cases were matched to controls on sex, age, and follow-up time. We measured serum Hcys, urinary As metabolites, and 26 SNPs in 13 OCM genes. Results: Serum Hcys and urinary %DMA were independently associated with increased and decreased odds of skin lesions, respectively. The T allele of MTHFR 677 C ➔ T (rs1801133) was associated with HHcys, higher %MMA, and lower %DMA, but not with skin lesions. Interactions between SNPs and water As on skin lesion risk were suggestive for three variants: the G allele of MTRR rs1801394 and T allele of FOLR1 rs1540087 were associated with lower odds of skin lesions with lower As (≤50 μg/L), and the T allele of TYMS rs1001761 was associated with higher odds of skin lesions with higher As. Conclusions: While HHcys and decreased %DMA were associated with increased risk for skin lesions, and MTHFR 677 C ➔ T was a strong predictor of HHcys, MTHFR 677 C ➔ T was not associated with skin lesion risk. Future studies should explore (i) non-OCM and non-genetic determinants of Hcys and (ii) if genetic findings are replicated in other As-exposed populations, mechanisms by which OCM SNPs may influence the dose-dependent effects of As on skin lesion risk. Highlights: Arsenic (As) is methylated to MMA and DMA via one-carbon metabolism (OCM). Elevated homocysteine (HHcys) is a marker of dysregulated OCM. HHcys and lower %DMA were independent risk factors for As-induced skin lesions. MTHFR C677T was associated with HHcys, %MMA, and %DMA, but not with skin lesions. Dysregulated OCM may influence susceptibility to As toxicity.